Growth Respond of Red Meranti on Width of Planting Line and Light Intensity in TPTJ Silvicultural System - Prijanto Pamoengkas; Febryandi Randana (Jurnal Silvikultur Tropika, 2013)
Shorea leprosula is one of red meranti species which included into target species and became pre-eminent in the silviculture intensive technique (SILIN), as well as having a good prospect to be developed as shorea plantation forest in Indonesia. This research aims to find out the growth of S. leprosula on width of planting line, crown closure, and light intensity in areal of TPTJ silvicultural system. This research was conducted in areal TPTJ that  consist of plantation of 2005, 2006, 2007, 2008, 2009, 2010, and 2011. Each plots consist of 100 x 100 m sized and selected 4 planting line for observation and measurement. The data of diameter and height of trees, width line, crown closure, and light intensity was collected during reseach time.Results showed that the growth of S. leprosula in TPTJ silvicultural system can be categorized as rapid growth with 1,32 cm/year average diameter increment, 1,61 cm/year height increment, and  86,57% percentage of live. The width of planting line effected to increase diameter and height with 5% value. Regression results showed that crown closure affect to S. leprosula diameter and height increment and light intensity affect to diameter increment. The best growth increment is at TPTJ 2009 plot with diameter increment is 1,63 cm/year and height increment is 1,91 m/year on 5 m width line, 77,71% crown closure, and light intensity of 10.632 lux.